Praktik dan Etika Wisata Religi di Solo Raya: Analisis Kualitatif Berbasis Islam Nusantara - Wahid Tuftazani Rizqi; Endang Purwasari; Saskia Eka Lestari (At Turots: Jurnal Pendidikan Islam, 2025)
Religious tourism in Indonesia is a socio-religious phenomenon that integrates Islamic spiritual values with local cultural traditions. In the context of Islam Nusantara, pilgrimage practices and religious rituals function as a means of cultural preservation as well as the formation of public ethics. The development of modern tourism then presented ethical challenges, such as the commercialization of religious sites and shifts in spiritual meaning. This research aims to analyze the form of religious tourism practices in Solo Raya, examine the principles of Islamic ethics implemented in pilgrimage and religious activities, and formulate a contextual and sustainable framework for Islamic religious tourism in the Nusantara. The research uses a qualitative approach through participatory observation, interviews, and document analysis. The research locations include five main sites: the Tomb of Sunan Pandanaran (Klaten), the Tomb of Mbah Sirodj (Solo), the Tomb of Yosodipuro (Boyolali), the Riyadh Mosque Tomb Complex (Surakarta), and the tradition of the Alms of the Cengklik Reservoir (Boyolali). The analysis was carried out with the framework of classical Islamic ethics (Al-Ghazali and Ibn Miskawaih) and the concept of Nusantara Islam which emphasizes harmony between religious teachings and local wisdom. The results of the study show that the practice of religious tourism in Solo Raya reflects three main layers of ethics: (1) spiritual ethics that emphasize sincerity and respect for sacred spaces, (2) social ethics that emphasize communal manners and responsibility, and (3) cultural ethics that display the integration of Islamic values and Javanese traditions. This research emphasizes that religious tourism is not only a spiritual activity, but also a means of character formation and strengthening social harmony. The recommendations are directed at the preparation of ethical guidelines for religious tourism based on Islamic values and local culture as the basis for sustainable religious tourism policies.